Botryllid species (Tunicata, Ascidiacea) from the Mediterranean coast of Israel, with some considerations on the systematics of Botryllinae - Brunetti, Riccardo (Zootaxa, 2009)
Several botryllid colonies of the genus Botrylloides from the Mediterranean coast of Israel are analysed. Three species are described: B. leachii, which differs because of its smaller size, from specimens collected from other European seas and is considered a case of dwarfism due to the particular hydrological conditions of the study area; B. anceps, a species originally described from the Indo-Pacific region, which probably migrated from the Red Sea; and Botrylloides israeliense, a new species. The distinction between the genera Botryllus and Botrylloides is discussed, and the original Milne-Edwards diagnosis based on differences in the structure of the system is recognised as still valid. Lastly, the diagnostic features usually employed in specific taxonomic determinations of Botryllinae are analysed.